Simultaneous Statistical Inference With Applications in the Life Sciences - Dickhaus, Thorsten; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This monograph will provide an in-depth mathematical treatment of modern multiple test procedures controlling the false discovery rate (FDR) and related error measures, particularly addressing applications to fields such as genetics, proteomics, neuroscience and general biology. The book will also include a detailed description how to implement these methods in practice. Moreover, new developments focusing on non-standard assumptions are also included, especially multiple tests for discrete data. The book primarily addresses researchers and practitioners but will also be beneficial for graduate students.
The problem of simultaneous inference -- Part I General Theory -- Some theory of p-values -- Classes of multiple test procedures -- Simultaneous test procedures -- Stepwise rejective multiple tests -- Multiple testing and binary classification -- Multiple testing and model selection -- Software solutions for multiple hypotheses testing -- Part II From Genotype to Phenotype -- Genetic association studies -- Gene expression analyses -- Functional magnetic resonance imaging -- Part III Further Applications in the Life Sciences -- Further life science applications.
Keywords: Life sciences; Data mining; Statistical methods; Mathematical statistics; Biomedical engineering; Life Sciences; Biostatistics; Statistical Theory and Methods; Mathematical and Computational Biology; Data Mining and Knowledge Discovery; Biomedical Engineering